Positional Accuracy Based on a Load Identification Optimization on a Linear Motor Sheet Forming Feeder - Nazrul Idzham, Kasim; A. R., Razali; Mohd Azam, Musa (Trans Tech Publications Inc., 2014)
Precision feeding is essential for micro-stamping, especially in multi-stage progressive forming operations, where necessary feeding rates also have to be maintained. Research in micro-stamping of thinner sheet metals (<100 microns) led to investigations of the performance of existing sheet-metal feeders, regarding their accuracy and repeatability in high speed micro-stamping. The results indicated that the pursuance of higher feeding accuracy and repeatability which aimed at 5-15% of the strip thickness was unachievable with the existing micro-feeders. A new high-precision and high-speed feeder was, therefore, developed for micro-sheet-forming. Initial non-optimized experimental results had showed high accuracy and repeatability were achieved.